PHYSICAL THERAPY IN MULTIPLE SCLEROSIS (Physical Culture and Sport: Scientific Perspective, 2024)
For many decades, multiple sclerosis (PC) has remained an urgent problem due to the rather high registration of this disease in the population, the defeat of mostly young people and their rapid disability. The article presents methods of rehabilitation of patients with MS.It is known that multiple sclerosis is a widespread autoimmune-inflammatory neurodegenerative disease of the central nervous system, which mainly affects young people and almost always leads to disability at a certain stage of development.This article provides an overview of the manifestations of multiple sclerosis, its form, and improvement of physical therapy methods for patients with multiple sclerosis. treatment and management of multiple sclerosis (MS). An overview of the clinical manifestations, pathomorphology, etiology and pathogenesis of the disease is provided, taking into account the role of the immune system in the development of MS.The article also presents an overview of modern treatment strategies, such as physiotherapy, emphasizing their effectiveness and possible side effects. The prospects of MS management are outlined, in particular, the development of new technologies and drugs to improve the quality of life of patients and reduce the progression of the disease.The article draws attention to the importance of an individualized approach to patients with MS and the use of modern research methods to improve the diagnosis and treatment of this disease.This article is aimed at the medical community and those interested in furthering the understanding of MS by providing a comprehensive view of current approaches to the diagnosis, treatment and management of this disease.Physical therapy in multiple sclerosis plays an important role in alleviating symptoms, preserving motor function, and improving patients' quality of life.
Keywords: multiple sclerosis; physical therapy; rehabilitation; physical exercises; disease